PUNAN LONGSEP: WACANA YANG BETERBANGAN PADA ORANG PUNAN DI TENGAH AREAL HAK GUNA USAHA DI KALIMANTAN TIMUR - Hermawan, Damasus Ferix Loys (Faculty of Humanities, Diponegoro University, 2018)
Punan Longsep is one of other original inhabitant of the forests on Borneo who depend their live of forest commodity. Their transition activities managing and obtaining forest product are disturbed by the transition of forest function. In Longsep (which is included in the transition areal of forest functions) there has been an interaction between Punan and HGU license holders or other groups. Interaction and communication thats led into various discourses to a variety of floating discourses. Furthermore, these discourses are negotiated to be part of the fulfillment of life needs. Many discourses have obtained by conducting live. Experience shows that there is a dominant discourse. Among discourses, there is a discourse that become a main role for Punanâ€™s life. This discourse reinforces the hypothesa that there is a dominantion for Punan. The domination seems in the changing of Punanâ€™s people. The main discourse domination that is appeared in their live is about â€œcompany discourseâ€. This discourse builds and shapes their life of Punans, that probably changes their orientation and perspective on companies in Longsep, that makes Punan only depend on the companies and can not do anything without the company. The dominance discourse seems to be the basic transformation of life practice for Punan.